Role of electrolytic hydrogen in smart city decarbonization in China. (15th April 2023) - Wang, Jianxiao; An, Qi; Zhao, Yue; Pan, Guangsheng; Song, Jie; Hu, Qinran; Tan, Chin-Woo
Graphical abstract: Highlights: A full-life-cycle optimization model of future city-level energy systems is developed. Feasibility of using power-to-hydrogen to achieve PV integration are highlighted. City-level hydrogen demand potentials in industry and transport are evaluated. Performances of two competing technologies of power-to-hydrogen (P2H) and electrochemical storage (ES) in carbon reductions are compared. Abstract: Distributed renewable energy is penetrating the urban energy system with a continuously increasing proportion. However, due to its natural randomness, a large number of energy storage resources are necessary. Electrolytic hydrogen could quickly follow the fluctuations of renewable energy and transform excess renewable energy into hydrogen stored for future use, which not only promotes the accommodation of renewable energy, but also drives the low-carbon development of construction, transportation, electricity, and other industries, thereby helping construct future low-carbon energy systems (FCES). However, few existing studies have conducted a systematic investigation on the role of electrolytic hydrogen in smart city decarbonization from both the supply and demand sides. Here, we develop a full-life-cycle optimization model of FCES with photovoltaic (PV) and power-to-hydrogen (P2H) planning to achieve decarbonization goals in China. Our results show that the annual hydrogen potential of 10 selected cities with different energy structures and quantities varies from 0.236 to 9.795 megatons, with a gap of more than 40-fold. Considering PV and P2H integration in FCES, the CO2 emissions of 10 cities in related fields decreased obviously under an 80 % photovoltaic penetration level (PPL). Compared with electrochemical storage, P2H shows better performance in PV integration of FCES from both economics and CO2 emissions. However, this advantage needs to be based on diverse terminal uses of electrolytic hydrogen.